Phenomenology Study of High School Students’ Experiences Who Do Suicidal-Attempt in Malang City, Indonesia - Yusfina Himayanti; Retty Ratnawati; Laily Yuliatun; Heni Dwi Windarwati (International Journal of Science and Society, 2020)
The objective of this study is to explore the experiences of high school students who are committing suicide in Malang, Indonesia. The study was qualitative research with an interpretive phenomenological approach and data analysis using IPA (Interpretative Phenomenological Analysis). Themes generated based on the results of the study include disappointment in the family as the basis of adolescent suicide, abuse from school friends triggers adolescents to think of suicide, and adolescents conduct suicide attempts spontaneously without planning. The results of this study indicate that many of the problems teenagers feel and think that trigger up causing teenagers to attempt suicide. The results of this study can also help us to better understand suicide attempts from the point of view of adolescents.